Fun English Class as an effort to improve English Literacy for Children at Elementary Level - Nurdianingsih, Fitri; Rozak, Refi Ranto; Rohmah, Ima Isnaini Taufiqur; Izza, Triananda Rahmatul (CV. Zabags Qu Publish, 2024)
The English Literacy Improvement Program for Children at the Elementary Level is a community service initiative that aims to improve the English reading and writing skills of elementary school children. This program is designed specifically for elementary school children, with an emphasis on areas that have high literacy needs. The implementation of this program uses the Asset-Based Community Development (ABCD) approach, which focuses on utilizing the assets and potential that exist within the community. In conclusion, this program succeeded in achieving its goals by increasing children's English literacy skills and providing long-term benefits for them and the community. Recommendations for further development include expansion of the program to other regions and continued support from government, schools and communities